Identification of suitable bread wheat (Triticum aestivum L.) lines for rainfed situation in Karnataka - Lohithaswa, H C; Biradar, S S; Naik, R V; Kalappanavar, I K; Patil, B N; Hanchinal, R R; Desai, S A (Journal of Cereal Research, 2011)
Karnataka is one of the important wheat growing statesin the peninsular India. Most of the area is under rainfedcondition dominated by durum wheat cultivation. In therecent years, the area under bread wheat is increasingunder rainfed condition. This necessitated the identificationof suitable lines for this situation. The success of anybreeding programme depends upon the successful selectionof genetically variable material in hand. To make theheritable improvement in characters, estimation of geneticparameters and genetic advance is required. Heritabilityestimates provides information about the extent to whicha particular character can be transmitted to the successivegenerations. Knowledge of heritability of a trait guides aplant breeder to predict behavior of succeeding generationsand helps in making desirable selections. Correlation studiesalong with path analysis provide a better understandingof the association of different characters with grain yield.Path coefficient analysis separates the direct effects fromthe indirect effects through other related characters byportioning the correlation coefficients (Dixet and Dubey,1984). The present study was carried out to evaluate thegenetic variability and inheritance of yield of some diverselines for the development of desirable wheat genotypes forthe rainfed areas.